Best Practice Democratic Policing in Papua: Activating Development and Security through Community Participation - Herjawan, Hery; Laksmono, Bambang Shergi; Robet, Robertus; Luthfi, Muhammmad; Putera, Vici Sofianna (Masyarakat: Jurnal Sosiologi, 2024)
The implementation of Democratic Policing across various parts of the world demonstrates the interconnectedness of changes in approaches to addressing security issues. This transformation is a result of a systemic shift from operational and managerial police systems. This research seeks to affirm this argument in the policing practices in Mimika, Papua, highlighting changes in the level of community participation in maintaining public safety and order driven by democratic policing practices in the region. This research employs a qualitative method for both data analysis and data collection. Data collection was conducted through interview techniques, meanwhile data analysis is conducted using case study. The results of this research indicate that the implementation of democratic policing in Mimika successfully activated other democratic instruments to be involved in conflict resolution in Papua.